Development of Ethanolic Extract of Pinang Masak Jambi (Areca Catechu L.) as A Modulator of Doxorubicin Cytotoxic Effect in Breast Cancer Therapy - Fitrianingsih, Fitrianingsih; Maharini, Indri; Utami, Diah Tri (UI Scholars Hub, 2020)
Doxorubicin is one of the chemotherapy agents that is often used in breast cancer therapy. Phenomenon of breast cancer cell resistance to chemotherapy agents has been traced to the molecular level. The development of compounds that can overcome drug resistance chemotherapy needs to be continuously developed, especially agents with specific molecular targets, namely P-glycoprotein (Pgp), NFkB, cyclin, and cyclin-dependent kinase (CDK). Another alternative is the combination of chemotherapy agents with chemopreventive agents (co-chemotherapy) to reduce side effects and increase sensitivity of cancer cells. Doxorubicin is often used in breast cancer therapy. This study was performed to determine the effect of ethanolic extract of Pinang Masak Jambi (Areca catechu L.) (EEPMJ) and doxorubicin combination on MCF-7 breast cancer cells. Cytotoxic assay of EEPMJ and doxorubicin, alone, or in combination, was done using MTT test method to determine the IC50 and CI (Combination Index) values. The results indicated that EEPMJ and doxorubicin had IC50 values of 75.1 µg/ml and 22 µg/ml, respectively. Based on CI values, all combination concentration showed varying CI values. The concentration of 1/8 IC50 of EEPMJ with 1/2, 1/4, and 1/8 IC50 of doxorubicin showed a strong synergistic effect (CI 0.1 - 0.3), with the inhibition of cell viability up to 67.39%. This synergistic effect occurs because EEPMJ potentially could increases the cytotoxicity of doxorubicin.